Knowledge of hand hygiene among nurses and physicians in three national hospitals of the Peruvian social health insurance, 2018 - Condor-Rojas, Yudy (2020)
Introduction: The hands of health care workers are the most common means of carrying the microorganisms responsible for healthcare-associated infections. The objective of our study was to evaluate the level of handwashing knowledge in three national social health insurance hospitals in metropolitan Lima, 2018. Material and Methods: During April-August 2018, we interviewed nurses and physicians from three national hospitals with a three-sections questionnaire to evaluate on a twenty-first scale the following domains: generalities, reasons for hand hygiene during health care, and situations to perform hand hygiene. Results: The median knowledge of nurses and physicians about hand hygiene was 13.41. The knowledge differs between nurses and physicians 13.3 vs. 13.6). Also, there was a lower frequency of success in the following items: hand disinfection lasts 20 to 30 seconds 54.1%, n=276), hand disinfection has 8 steps 52.9%, n=270), elimination of transitory skin microorganisms 47.1%, n=240), when there is an infectious diagnosis 34.7%, n=177). Conclusion: The knowledge of nurses and physicians was low and there is a difference between professional subgroups. It is recommended to implement continuous training following the WHO multimodular strategies.